2020
DOI: 10.1515/ijamh-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nutrition education in improving fruit and vegetable consumption among selected college students in urban Puducherry, South India. A pre-post intervention study

Abstract: ObjectivesWorld Health Organization (WHO) suggests intake of five servings (400 g) of fruits and vegetables (F&V) per day to ensure an adequate dietary fibre and to reduce the risk of non-communicable diseases. Risk factor survey of Non-Communicable Diseases (2007–08), reports that only 1% population in Tamil Nadu, South India consumed more than five servings a day. So we aimed to assess the effectiveness of nutrition education in improving the daily intake of fruit and vegetable servings and stage of beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Additionally, studies suggest the need to expand the food subsidy programs under the National Food Security Act (NFSA) [ 30 ], and the need to include the nutrient-rich food groups in these programs [ 31 ]. To improve consumer practices and awareness related to fruit and vegetable consumption, specific interventions [ 32 ] and nutrition education campaigns [ 33 , 34 ] have also been found to be effective to a certain extent. Overall, a comprehensive holistic approach with targeted interventions will be helpful for improving the consumption of nutrient-rich foods and attaining food security over time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies suggest the need to expand the food subsidy programs under the National Food Security Act (NFSA) [ 30 ], and the need to include the nutrient-rich food groups in these programs [ 31 ]. To improve consumer practices and awareness related to fruit and vegetable consumption, specific interventions [ 32 ] and nutrition education campaigns [ 33 , 34 ] have also been found to be effective to a certain extent. Overall, a comprehensive holistic approach with targeted interventions will be helpful for improving the consumption of nutrient-rich foods and attaining food security over time.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the previous studies which also reported similar results. [ 26 27 28 ] The possible explanation could be that the tailored intervention package, interactive session and self-explanatory pamphlet helped the participants to alter their behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Email: dhana.ibms@gmail.com spite the Covid19 pandemic, Earlier it has been reported that 99% of people in Tamil Nadu only consumes less than five servings of fruits and vegetables in a day [17,18]. The diary products, fruits and dark green leafy vegetables were believed to be more expensive and there was a decrease in consumption of pulses, whole grain cereals, vegetables, fruits with the gradual increase in intake of meat products since from 1970s.…”
Section: Jagadeesan Thanalakshmimentioning
confidence: 99%